Implementation of Project-Based Learning to Improve Students' Critical and Collaborative Thinking Skills in Database Subjects in the Independent Curriculum - Nixson Jeheskial Meok; Ichsan Fahmi; Godlief Erwin S. Mige; Katarina Sriayu Intan Narek (Journal of Educational Management Research, 2026)
This study investigates the effect of the Project-Based Learning (PjBL) model on students' critical thinking skills, with collaborative ability acting as an intervening variable, in the context of the Merdeka Curriculum for the Database subject in vocational education. This research was conducted at SMKN 6 Kupang involving 60 eleventh-grade students of the Software and Game Development (PPLG) program. A quantitative approach was employed using path analysis to examine both direct and indirect relationships among variables. The findings of Model 1 indicate that the PjBL model has a significant positive effect on students' collaborative ability (β = 0.390, p < 0.05), explaining 15.2% of the variance. Furthermore, Model 2 reveals that the PjBL model significantly influences students' critical thinking skills both directly and indirectly through collaborative ability. Collaborative ability was found to have a significant effect on critical thinking skills and partially mediates the relationship between PjBL and critical thinking. These results suggest that PjBL not only directly enhances students' critical thinking skills but also strengthens them indirectly by fostering effective collaboration during project implementation. Therefore, the integration of PjBL in vocational learning, particularly in Database subjects, is effective in supporting the development of critical thinking and collaborative competencies required in 21st-century learning and the Merdeka Curriculum framework.